Design and Construction of Automatic Planting Device Using NodeMCU Based on Internet of Things - Nur, Muhammad Arifin; Hariyono, Rito Cipta Sigitta; Sorikhi, Sorikhi (Journal of World Science, 2022)
Advances in science and technology have provided enormous benefits in helping human work, including in watering plants. Given the importance of the benefits of technological developments based on real life, that automatic watering using sensors has replaced traditional methods with human power in carrying out daily activities and in the industrial sector. In this study, hardware and software for an automatic watering control system will be built. The research method uses a literature study approach in the form of books and research reports related to the system to be designed. The automatic watering device is built based on the NodeMCU ESP8266 microcontroller and is equipped with a soil moisture sensor. Based on the experimental results, the automatic sprinkler as a means of facilitating plant care using a soil moisture sensor works well according to the program entered, where when the humidity value is above 85 the device will water automatically and if the humidity value is below 85 the device will stop watering.